Extending Hadoop's Yarn Scheduler Load Simulator with a highly realistic network & traffic model - Wette, Philip; Schwabe, Arne; Splietker, Malte; Karl, Holger (Proceedings of the 1st IEEE Conference on Network Softwarization, NetSoft 2015, London, United Kingdom, April 13-17, 2015)

Flexible reassignment of flow processing-aware controllers in future wireless networks - Auroux, Sébastien; Karl, Holger (26th IEEE Annual International Symposium on Personal, Indoor, and Mobile Radio Communications, PIMRC 2015, Hong Kong, China, August 30 - September 2, 2015)

Efficient flow processing-aware controller placement in future wireless networks - Auroux, Sébastien; Karl, Holger (2015 IEEE Wireless Communications and Networking Conference, WCNC 2015, New Orleans, LA, USA, March 9-12, 2015)

Specification of Complex Structures in Distributed Service Function Chaining Using a YANG Data Model - Dräxler, Sevil; Karl, Holger (CoRR)

Dynamic Backhaul Network Configuration in SDN-based Cloud RANs - Dräxler, Martin; Karl, Holger (CoRR)

An Architecture for Energy-aware On-demand Mobile Network Management - Peuster, Manuel; Karl, Holger (Proceedings of the 5th Workshop on All Things Cellular: Operations, Applications and Challenges)
The increasing amount of mobile traffic leads to a significantly higher energy consumption of mobile networks that is mainly caused by the high number of required base stations. One recent solution for this is based on a two-layered network that uses long-range macro cells to provide a full coverage signaling overlay and short-range small cells for fast data transmissions. These small cells can be switched off when they are not needed and allow network-wide energy optimizations. This paper presents an architecture that extends existing mobile networks to integrate a small cell layer that supports on-demand cell activation. We discuss how additional small cells can be interconnected with existing core components and how they can be controlled by a resource management component. Finally, a Wi-Fi based proof of concept testbed implementation is presented that demonstrates the feasibility of the approach.

Dynamic network reconfiguration in wireless DenseNets with the CROWD SDN architecture - Auroux, Sébastien; Draxler, Martin; Morelli, Arianna; Mancuso, Vincenzo (2015 European Conference on Networks and Communications (EuCNC))

MaxiNet: Distributed Emulation of Software-Defined Networks - Wette, Philip; Dräxler, Martin; Schwabe, Arne; Wallaschek, Felix; Zahraee, Mohammad Hassan; Karl, Holger (Proceedings of the 2014 IFIP Networking Conference (Networking 2014))
Network emulations are widely used for testing novel network protocols and routing algorithms in realistic scenarios. Up to now, there is no emulation tool that is able to emulate large software-deﬁned data center networks that consist of several thousand nodes. Mininet is the most common tool to emulate Software-Deﬁned Networks of several hundred nodes. We extend Mininet to span an emulated network over several physical machines, making it possible to emulate networks of several thousand nodes on just a handful of physical machines. This enables us to emulate, e.g., large data center networks. To test this approach, we additionally introduce a trafﬁc generator for data center trafﬁc. Since there are no data center trafﬁc traces publicly available we use the results of two recent trafﬁc studies to create synthetic trafﬁc. We show the design and discuss some challenges we had in building our trafﬁc generator. As a showcase for our work we emulated a data center consisting of 3200 hosts on a cluster of only 12 physical machines. We show the resulting workloads and the trade-offs involved.

Using Application Layer Knowledge in Routing and Wavelength Assignment Algorithms - Wette, Philip; Karl, Holger (Proceedings of the IEEE International Conference on Communications 2014)
Preemptive Routing and Wavelength Assignment (RWA) algorithms preempt established lightpaths in case notenough resources are available to set up a new lightpath in aWavelength Division Multiplexing (WDM) network. The selectionof lightpaths to be preempted relies on internal decisions of theRWA algorithm. Thus, if dedicated properties of the networktopology are required by the applications running on the network,these requirements have to be known to the RWA algorithm.We present a family of preemptive RWA algorithms for WDMnetworks. These algorithms have two distinguishing features: a)they can handle dynamic traffic by on-the-fly reconfiguration,and b) users can give feedback for reconfiguration decisions andthus influence the preemption decision of the RWA algorithm,leading to networks which adapt directly to application needs.This is different from traffic engineering where the network is(slowly) adapted to observed traffic patterns.Our algorithms handle various WDM network configurationsincluding networks consisting of heterogeneous WDM hardware.To this end, we are using the layered graph approach togetherwith a newly developed graph model that is used to determineconflicting lightpaths.

Tragedy of the Common Cloud - Game Theory on the Infrastructure-as-a-Service Market - Künsemöller, Jörn

Template Embedding: Using Application Architecture to Allocate Resources in Distributed Clouds - Keller, Matthias; Robbert, Christoph; Karl, Holger (Proceedings of 7th International Conference on Utility and Cloud Computing (UCC))
In distributed cloud computing, application deployment across multiple sites can improve quality of service. Recent research developed algorithms to find optimal locations for virtual machines. However, those algorithms assume to have either single-tier applications or a fixed number of virtual machines – a strong simplification of reality. This paper investigates the placement and scaling of complex application architectures. An application is dynamically scaled to fit both the current demand situation and the currently available infrastructure resources. We compare two approaches: The first one is based on virtual network embedding. The second approach is a novel method called Template Embedding. It is based on a hierarchical 1-allocation hub flow problem and combines applica- tion scaling and embedding in one step. Extensive experiments on 43200 network configurations showed that Template Embedding outperforms virtual network embedding in all cases in three metrics: success rate, solution quality, and runtime. This positive result shows that template embedding is a promising approach for distributed cloud resource allocation.

Specifying and Placing Chains of Virtual Network Functions - Dräxler, Sevil; Keller, Matthias; Karl, Holger (Proceedings of the 3rd International Conference on Cloud Networking (CloudNet))
Network appliances perform different functions on network flows and constitute an important part of an operator’s network. Normally, a set of chained network functions process network flows. Following the trend of virtualization of networks, virtualization of the network functions has also become a topic of interest. We define a model for formalizing the chaining of network functions using a context-free language. We process deployment requests and construct virtual network function graphs that can be mapped to the network. We describe the mapping as a Mixed Integer Quadratically Constrained Program (MIQCP) for finding the placement of the network functions and chaining them together considering the limited network resources and requirements of the functions. We have performed a Pareto set analysis to investigate the possible trade-offs between different optimization objectives.

Simulating load-dependent operation of picocells - Roeske, Daniel

Response Time-Optimized Distributed Cloud Resource Allocation - Keller, Matthias; Karl, Holger (Proceedings of the SIGCOMM workshop on Distributed cloud computing)
In the near future many more compute resources will be available at different geographical locations. To minimize the response time of requests, application servers closer to the user can hence be used to shorten network round trip times. However, this advantage is neutralized if the used data centre is highly loaded as the processing time of re- quests is important as well. We model the request response time as the network round trip time plus the processing time at a data centre.We present a capacitated facility location problem formal- ization where the processing time is modelled as the sojourn time of a queueing model. We discuss the Pareto trade-off between the number of used data centres and the resulting response time. For example, using fewer data centres could cut expenses but results in high utilization, high response time, and smaller revenues.Previous work presented a non-linear cost function. We prove its convexity and exploit this property in two ways: First, we transform the convex model into a linear model while controlling the maximum approximation error. Sec- ond, we used a convex solver instead of a slower non-linear solver. Numerical results on network topologies exemplify our work.

Reducing Energy Consumption of Radio Access Networks - Herlich, Matthias
Radio access networks (RANs) have become one of the largest energy consumers of communication technology [LLH+13] and their energy consumption is predicted to increase [FFMB11]. To reduce the energy consumption of RANs different techniques have been proposed. One of the most promising techniques is the use of a low-power sleep mode. However, a sleep mode can also reduce the performance. In this dissertation, I quantify how much energy can be conserved with a sleep mode and which negative effects it has on the performance of RANs. Additionally, I analyze how a sleep mode can be enabled more often and how the performance can be kept high. First, I quantify the effect of power-cycle durations on energy consumption and latency in an abstract queuing system. This results in a trade-off between energy consumption and latency for a single base station (BS). Second, I show that considering a network as a whole (instead of each BS individually) allows the energy consumption to be reduced even further. After these analyses, which are not specific for RANs, I study RANs for the rest of the dissertation. RANs need to both detect and execute the requests of users. Because detection and execution of requests have different requirements, I analyze them independently. I quantify how the number of active BSs can be reduced if the detection ranges of BSs are increased by cooperative transmissions. Next, I analyze how more BSs can be deactivated if the remaining active BSs cooperate to transmit data to the users. However, in addition to increasing the range, cooperative transmissions also radiate more power. This results in higher interference for other users which slows their transmissions down and, thus, increases energy consumption. Therefore, I describe how the radiated power of cooperative transmissions can be reduced if instantaneous channel knowledge is available. Because the implementation in real hardware is impractical for demonstration purposes, I show the results of a simulation that incorporates all effects I studied analytically earlier. In conclusion, I show that a sleep mode can reduce the energy consumption of RANs if applied correctly. To apply a sleep mode correctly, it is necessary to consider power-cycle durations, power profiles, and the interaction of BSs. When this knowledge is combined the energy consumption of RANs can be reduced with only a slight loss of performance. Because this results in a trade-off between energy consumption and performance, each RAN operator has to decide which trade-off is preferred.

Provider Competition in Infrastructure-as-a-Service - Künsemöller, Jörn; Brangewitz, Sonja; Karl, Holger; Haake, Claus-Jochen (Proceedings of the 2014 IEEE International Conference on Services Computing (SCC))
This paper explores how cloud provider competition inﬂuences instance pricing in an IaaS (Infrastructure-as-a-Service) market. When reserved instance pricing includes an on-demand price component in addition to a reservation fee (two-part tariffs), different providers might offer different price combinations, where the client’s choice depends on its load proﬁle. We investigate a duopoly of providers and analyze stable market prices in two-part tariffs. Further, we study offers that allow a speciﬁed amount of included usage (three-part tariffs). Neither two-part nor three-part tariffs produce an equilibrium market outcome other than a service pricing that equals production cost, i.e., complex price structures do not signiﬁcantly affect the results from ordinary Bertrand competition.

Incorporating feedback from application layer into routing and wavelength assignment algorithms - Wette, Philip; Karl, Holger (2013 IEEE Conference on Computer Communications Workshops (INFOCOM WKSHPS))

Anticipatory Power Cycling of Mobile Network Equipment for High-Demand Multimedia Traffic - Dreimann, Philipp

Adaptive Placement of Programmable Virtual Network Function Chains - Dräxler, Sevil

A Game-Theoretic Approach to the Financial Benefits of Infrastructure-as-a-Service - Künsemöller, Jörn; Karl, Holger (Future Generation Computer Systems)
Financial beneﬁts are an important factor when cloud infrastructure is considered to meet processing demand. The dynamics of on-demand pricing and service usage are investigated in a two-stage game model for a monopoly Infrastructure-as-a-Service (IaaS) market. The possibility of hybrid clouds (public clouds plus own infrastructure) turns out to be essential in order that not only the provider but also the clients have signiﬁcant beneﬁts from on-demand services. Even if the client meets all demand in the public cloud, the threat of building a hybrid cloud keeps the instance price low. This is not the case when reserved instances are oﬀered as well. Parameters like load proﬁles and economies of scale have a huge eﬀect on likely future pricing and on a cost-optimal split-up of client demand between either a client’s own data center and a public cloud service or between reserved and on-demand cloud instances.